Moving to the Beat and Singing are Linked in Humans - Dalla Bella, Simone; Berkowska, Magdalena; Sowiński, Jakub (Frontiers in Human Neuroscience, 2015)
The abilities to sing and to move to the beat of a rhythmic auditory stimulus emerge early during development, and both engage perceptual, motor, and sensorimotor processes. These similarities between singing and synchronization to a beat may be rooted in biology. Patel (2008) has suggested that motor synchronization to auditory rhythms may have emerged during evolution as a byproduct of selection for vocal learning (“vocal learning and synchronization hypothesis”). This view predicts a strong link between vocal performance and synchronization skills in humans. Here we tested this prediction by asking occasional singers to tap along with auditory pulse trains and to imitate familiar melodies. Both vocal imitation and synchronization skills were measured in terms of accuracy and precision or consistency. Accurate and precise singers tapped more in the vicinity of the pacing stimuli (i.e., they were more accurate) than inaccurate and imprecise singers. Moreover, accurate singers were more consistent when tapping to the beat. These differences cannot be ascribed to basic motor skills or to motivational factors. Individual differences in terms of singing proficiency and synchronization skills may reflect the variability of a shared sensorimotor translation mechanism.